SELF-EFFICACY GURU PENDIDIKAN AGAMA ISLAM DALAM MENERAPKAN PEMBELAJARAN BERBASIS DEEP LEARNING - Syamsul Arifin; Devid Dwi Erwahyudin; Sri Susanti; Yusuf Hamdani Abdi; Rusmi (Program Studi Manajemen Pendidikan, 2025)
This study aims to analyze the self-efficacy level of Islamic Religious Education (PAI) teachers and identify factors that influence the implementation of deep learning-based learning at Muhammadiyah 1 High School, Ponorogo. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, participatory observation, and documentation studies of eight PAI teachers. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña which includes the stages of reduction, presentation, and conclusion drawing. The results show that the level of self-efficacy of Islamic Religious Education (PAI) teachers is in the medium to high category with variations in three main dimensions : learning planning (high), implementation (medium-high), and challenge management (medium). The most dominant strengthening factors are mastery experience through successful experiences and social persuasion through collegial support, while inhibiting factors include administrative burden, limited practice models, and physiological fatigue due to workload. Overall, teacher self-efficacy acts as a catalyst for pedagogical transformation from conventional approaches to contextual, reflective, and character-based deep learning.